MULTIDISCIPLINARY APPROACHES TO STUDYING THE PHENOMENON OF LEADERSHIP - L. Mosina; D. Veselovskiy (Вестник университета)
The main approaches to the study of leadership are presented. The modern trend of the phenomenon under study are considered. The importance of interdisciplinary studying and teaching leadership are reasoned.